Center of excellence for mobile sensor data-to-knowledge (MD2K). (3rd July 2015) - Kumar, Santosh; Abowd, Gregory D; Abraham, William T; al'Absi, Mustafa; Gayle Beck, J; Chau, Duen Horng; Condie, Tyson; Conroy, David E; Ertin, Emre; Estrin, Deborah; Ganesan, Deepak; Lam, Cho; et al.
Abstract: Mobile sensor data-to-knowledge (MD2K) was chosen as one of 11 Big Data Centers of Excellence by the National Institutes of Health, as part of its Big Data-to-Knowledge initiative. MD2K is developing innovative tools to streamline the collection, integration, management, visualization, analysis, and interpretation of health data generated by mobile and wearable sensors. The goal of the big data solutions being developed by MD2K is to reliably quantify physical, biological, behavioral, social, and environmental factors that contribute to health and disease risk. The research conducted by MD2K is targeted at improving health through early detection of adverse health events and by facilitating prevention. MD2K will make its tools, software, and training materials widely available and will also organize workshops and seminars to encourage their use by researchers and clinicians.